2006
DOI: 10.1182/blood-2006-03-011106
|View full text |Cite
|
Sign up to set email alerts
|

KLF4 suppresses transformation of pre-B cells by ABL oncogenes

Abstract: IntroductionThe Krüppel-like factor (KLF) family of transcription factors is related to the protein Krüppel in Drosophila melanogaster. 1,2 KLFs regulate cell-fate decisions, including development and differentiation of specific tissues. Each contains 3 conserved zinc finger DNA-binding motifs in the c-terminal domain and bind GC-rich regions with a consensus sequence of "CACCC." The functional specificity of distinct KLF family members is maintained through the transactivation and/or repression domains in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
54
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 53 publications
6
54
0
Order By: Relevance
“…Application of COPA to the expression profiles of the 136 human AML cases demonstrated that of the putative CDX2 effectors shown in Figure 1C, only KLF4 and G0S2 were among the top-ranking outliers at the 95th percentile, showing markedly decreased expression in patients with high CDX2 mRNA levels ( Figure 1D). These observations, together with previous data showing that KLF4 functions as a tumor suppressor in certain gastrointestinal cancers (32)(33)(34) and B cell malignancies (35,36), suggested that suppression of KLF4 might be one mechanism whereby CDX2 promotes leukemogenesis.…”
Section: Derivation Of a Gene Signature Associated With Cdx2 Expressimentioning
confidence: 84%
“…Application of COPA to the expression profiles of the 136 human AML cases demonstrated that of the putative CDX2 effectors shown in Figure 1C, only KLF4 and G0S2 were among the top-ranking outliers at the 95th percentile, showing markedly decreased expression in patients with high CDX2 mRNA levels ( Figure 1D). These observations, together with previous data showing that KLF4 functions as a tumor suppressor in certain gastrointestinal cancers (32)(33)(34) and B cell malignancies (35,36), suggested that suppression of KLF4 might be one mechanism whereby CDX2 promotes leukemogenesis.…”
Section: Derivation Of a Gene Signature Associated With Cdx2 Expressimentioning
confidence: 84%
“…: (25)(26)(27)(28)(29)(30)(31)(32). Because of its known role as a transcription factor, we sought to systematically determine how it interacted with the IL-6 promoter.…”
Section: Discussionmentioning
confidence: 99%
“…with a KLF4 signal ≥mean value + 2 SD in normal BMPC) and 30% of the patients had a very weak KLF4 signal <100. The KLF4 gene was not expressed by any of 18 HMCL (median value 5, range [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Using western blot analysis, KLF4 protein could be detected in the five samples of purified primary MMC in which the KLF4 gene was expressed (Online Supplementary Figure S1B).…”
Section: Klf4 Was Expressed In Purified Cd14mentioning
confidence: 99%
“…3 However, KLF4 is also a so-called stem cell protein. It is one of Yamanaka's four proteins (OCT4, SOX2, KLF4 and MYC) able to reprogram adult cells into induced pluripotent stem cells.…”
Section: Introductionmentioning
confidence: 99%